Merging and diverging cultures in M&A. Issue 9 (12th September 2016) - Mielly, Michelle; Alain Rouault, Frank; Richards O'Reilly, Kevin
Abstract : Purpose: The purpose of this brief paper is to highlight the role of culture in cross-cultural M&A environments. Findings: Empirical work as consultants and participant-observers within multiple international organizations in the process of pre or post M&A restructuring has revealed the need to develop three key "best practices" linked to behaviors which facilitate organizational actors' role in such dynamic and complex organizational environments. Practical implications: Managers and practitioners may be able to re think their own positioning within the merged or merging firm and question some of their own cultural allegiances and behaviors, whether linked to national culture or organizational (corporate) culture. Originality/value: The authors have identified three key behavioral skills crucial to effective intercultural interactions, when interacting in cross-border M&A contexts.